Teachers’ Directive Speech Acts in the Classroom Interaction Discourse of Children with Hearing Impairment - Ardianto Ardianto (Jurnal Pendidikan Humaniora, 2014)
Tindak Tutur Direktif Guru dalam Wacana Interaksi Kelas Anak TunarunguAbstract: This research discusses about teachers’ use of directive speech acts in the discourse of classroom interaction children with hearing impairment. This research uses qualitative approach. The results are that directive speech acts in discourse interaction of classroom teachers of children with hearing impairment variously expressed through form, function, and speak a specific strategy. Form, function, and the directive speech act strategies that teachers expressed based on the diversity of contexts that underlie the discourse of conversation in the classroom.Key Words: directive acts, classroom interaction, hearing impaired children, discourse Abstrak: Penelitian ini membahas tentang penggunaan tindak tutur direktif guru dalam wacana interaksi kelas anak tunarungu. Penelitian ini menggunakan pendekatan kualitatif. Hasilnya adalah bahwa tindak tutur direktif guru dalam wacana interaksi kelas anak tunarungu diekspresikan secara beragam melalui bentuk, fungsi, dan strategi bertutur tertentu. Bentuk, fungsi, dan strategi tindak tutur direktif yang diekspresikan guru mempunyai kecenderungan keefektifan yang berbeda-beda berdasarkan pada keragaman konteks yang melatari wacana interaksi kelas anak tunarungu.Kata kunci: tindakan direktif, interaksi kelas, pendengaran anak cacat, wacana